Future needs for energy storage in the alpine region - Hočevar, Marko (Acta hydrotechnica, 2019)
In this paper we discuss energy storage requirements for EUSALP region in Europe. EUSALP is an Alpine region that includes the entirety Switzerland, Austria, Slovenia, and Lichtenstein, as well as parts of France, Germany, and Italy. A model is presented that facilitates the estimation of the required technical amounts of energy storage and installed power of pumped storage hydropower plants. The aim of the model is to estimate the requirements of energy storage to assist in setting guidelines for stable and reliable future electric energy supply in the EUSALP region. The model is based on currently known patterns of energy consumption and generation and available information on the future increase of renewable electric generation capacity, energy consumption, and the introduction of electromobility within all EUSALP regions. The hourly balance of generation, demand, and storage within a selected future year is assumed. The results are presented such that a mix of scenarios is addressed. Among them are installed generation capacity, installed pumped hydro storage power, selection of photovoltaic and wind electric energy generation ratio, the charging of a selected percentage of electric cars, flexible run-of-river hydro electric energy generation, import/export, generation by nuclear and backup fossil fuel sources, and a selection of disturbances. Results show that energy storage capacities must be increased by a large margin regardless of the choice of demand site management strategies or flexible electric car charging. Around a requisite 10-fold increase in pumped storage hydropower capacity is estimated, while the estimated increase in required energy storage is even higher. Daily and seasonal variations are also discussed. Further, the amount of surplus electric energy generation is presented and discussed.
Keywords: črpalno akumulacijske hidroelektrarne; energy storage; EUSALP; EUSALP region; fotovoltaika; photovoltaics; pumped storage hydropower plants; shranjevanje energije; veter; wind